Simulação do conforto térmico do pedestre no ambiente urbano - Nakata, Camila Mayumi [UNESP]; Souza, Léa Cristina Lucas de [UNESP]; Faria, João Roberto Gomes de [UNESP] (My University, 2010)
This paper presents a pilot study carried out for an urban ergonomic investigation, considering the pedestrian point of view in relation to the thermal comfort. Therefore, a thermal evaluation of an urban fraction is performed, by applying simulations in the ENVI-met model, associated with the application of the BOTworld software.

Este artigo apresenta um estudo piloto realizado para a investigação da ergonomia urbana sob o ponto de vista do pedestre em relação ao conforto térmico. Para isso é feita uma avaliação térmica de uma fração urbana através de simulações no modelo ENVI-met, associada à aplicação do programa BOTworld.
Keywords: Urban ergonomics; Environmental ergonomics; Thermal comfort; Ergonomia urbana; Ergonomia ambiental; Conforto térmico